(untitled) (Research, Society and Development, 2020)
Cocos nucifera (L) or green coco, which belongs to the Palmae family, is a palm tree, originating in Southeast Asia, which was introduced to Brazil in 1553. This study analyzed the drying process of green coconut albumen, using the diffusion model and determined the enthalpy of water sorption of fresh green coconut albumen. For the modeling of the experimental data, the diffusive model (Fick’s Second Law) adapted the flat plate geometry for drying kinetics and two mathematical models for the theoretical and empirical isotherms. By modeling nonlinear regression drying, it was possible to obtain the values of the effective diffusion coefficients for each temperature. The temperature increase favored the mass transfer process, so the temperature of 60 °C was more adequate in drying. The GAB and Halsey models presented the best simulation of the experimental data of the isotherms, but because the Halsey model was a more appropriate model for agricultural products, it was chosen, presenting R2 > 0.98 and MSE < 0.032 and, thus, the parameters of it were used to determine the enthalpy of water sorption. The Clausius-Clapeyron equation was applied to a constant moisture content to determine the sorption enthalpy of the green coconut albumen. The most homogeneous points, in terms of energy, were found in the moisture content range of 1.157 to 1.633 kg/kg b.s., where the maximum enthalpy value equal to 338.92 kJ/mol was obtained.